The Technique of Determining Ijtihad and Its Application In Life: Analysis Of Istihsan, Maslahah Mursalah, 'Urf, and Syar'u Man Qablana - Ahmad Maulidizen; Ashilah Raihanah (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2019)
Islam as a comprehensive religion has regulated the Shari'a for the conduct of all human actions which the Shari'a is universal and its use is not limited by the times. There are four main sources in the determination of law in Islam, namely Alquran, Sunnah, Ijma and Qiyas. Apart from the source of the law, there are several methods used by ulul Usul Fiqh to determine the law on a new problem. The issue in this research is whether the methods of ijtihad such as Istihsan, Maslahah Mursalah, Urf, and Syar'u man qablana can be accepted and allowed by the Ulema Ushul fiqh in determining a law? What is the success in Islamic law? And how is it applied in human life and activity? The method used in this paper is the library study method. The results of the research obtained that Istihsan, Maslahah Mursalah, Urf, and Syar'u man qablana are part of Islamic Shari'a. Despite the differences of opinion among the scholars regarding the ability to use the ijtihad methods. There are those who directly allow, some also give certain conditions in the process of determining the law. Described the arguments that strengthen the opinions of the scholars in issuing their fatwa. There are also examples of the implementation and application of the ijtihad method both at the time of the Prophet's best friend and in the present in accordance with the true Islamic Shari'a